EVALUASI KINERJA BAPPEDA-LITBANG KABUPATEN KAUR DALAM PROSES PENYUSUNAN RENCANA KERJA PEMBANGUNAN - Dani, Rahiman; Sislan, Sislan; Aprianty, Henny; Noviyanto, Hernowo (Perkumpulan Dosen Muda (PDM) Bengkulu, 2023)
The purpose of this study is to describe, know and understand the results of the evaluation of the performance of BAPPEDA-LITBANG of Kaur Regency in preparing very good development plans. Methods This research will be conducted using a qualitative research approach. , without carrying out any treatment or manipulation of the variables being studied. Qualitative descriptive research is a type of research that aims to describe existing conditions by collecting data objectively. Meanwhile, to gather information in this study, the methods used are observation, interviews, and documentation. Triangulation with 6 informants at the BAPPEDA LITBANG office in Kaur District. Data analysis was carried out by comparing theory and practice. The analysis focused on variables related to evaluating the performance of BAPPEDA-LITBANG in Kaur district in the process of preparing a development work plan. From the results of research that has been carried out by expert researchers, the conclusions in this study are. evaluation of the performance of the Research and Development Agency of Kabuaten Kaur in the process of preparing the development work plan has been effective and efficient.